Metagenomics Reveals Seasonal Functional Adaptation of the Gut Microbiome to Host Feeding and Fasting in the Chinese Alligator - Tang, Ke-Yi; Wang, Zhen-Wei; Wan, Qiu-Hong; Fang, Sheng-Guo (Frontiers in Microbiology, 2019)
Hibernator gut microbiomes vary seasonally with host physiology and food availability, but their functional potential and host–microbial interactions have not been well characterized. As a natural hibernator, the Chinese alligator (Alligator sinensis) is an ideal and intriguing model to investigate changes in microbial community structure and function caused by hibernation. In this study, we used 16S rRNA profiling and metagenomic analysis to compare the microbiome composition, diversity, and functional capacity in the gut of hibernating versus active Chinese alligators. Our results show that gut microbial communities undergo seasonal restructuring in response to seasonal cycles of feeding and fasting in the Chinese alligator, but this animal harbors a core gut microbial community primarily dominated by Proteobacteria, Fusobacteria, Bacteroidetes and Firmicutes across the gut regions. During hibernation, there is an increase in the abundance of bacterial taxa (e.g., Bacteroidetes) that can degrade and utilize host mucin glycans, which allows adaptation to winter fasting. This is accompanied by the enrichment of mucin oligosaccharide-degrading enzyme and carbohydrate-active enzyme families. In contrast, during the active phase (feeding), active Chinese alligators exhibit a carnivore gut microbiome dominated by Fusobacteria, and there is an increase in the relative abundance of bacteria (e.g., Cetobacterium somerae) with known proteolytic and amino acids-fermentating functions that improve host protein-rich food digestion efficiency. In addition, seasonal variations in the expression of β-defensins play a protective role in intestinal immunity. These findings provide insights into the functional adaptations of host–gut microbe symbioses to seasonal dietary shifts to maintain gut homeostasis and health, especially in extreme physiological states.